(untitled) (Revista Educação, Artes e Inclusão, 2025)
Contemporary choreographic creation has, in itself, a potential for multiplicity, that is, capable of being a place of continuous reconfiguration and slippage. However, there is a stability in the methods and processes of choreographic creation that corresponds to the relational aspect. Where the choreographic work exists in the relationship between agents: audience, performers, creators, teachers, mediators. This text proposes to think about and describe the Dançar Arte Project that articulates the Modern Art Center of the Gulbenkian Foundation and the Higher School of Dance of the Polytechnic Institute of Lisbon. Thus, in addition to a description of the project, in its different branches and spheres: expository, performance and training; intends to expand and think about its methodological aspects and their consequences. Where, starting from Nicolas Bourriaud’s relational aesthetics, it is possible to look at creation as a meeting place. And address the importance of creating experiences that promote learning and reflection through art, highlighting how these creation processes in museums can stimulate dialogue between artists, visitors and works. Founding a collaborative perspective of choreographic creation in a museum context. Where, to the detriment of a figure of power, associated with the authorship of a work, a horizontal field of relationships is proposed, and a process of creation-interpretation is guided. In which the role of artistic education is linked to the search for singularity and the meeting of the inner world of the agents of creation and the outer world of the works, enhancing ethical, aesthetic and political experiences.